(untitled) (The Review of Diabetic Studies, 2025)
Cardiovascular diseases remain a major global public health challenge, requiring preventive strategies that extend beyond traditional diagnosis and treatment. Early cardiovascular risk recognition depends not only on identifying established risk factors such as hypertension, diabetes mellitus, dyslipidemia, smoking, obesity, and physical inactivity, but also on recognizing broader clinical, behavioral, oral, and medication-related indicators that may appear during routine patient encounters. Oral health, particularly periodontal health, provides an accessible and often underused gateway for identifying patients with shared cardiometabolic, inflammatory, behavioral, and social risk factors. At the same time, medication review offers a practical pathway for identifying poor adherence, uncontrolled risk factors, bleeding concerns, adverse drug effects, drug interactions, and gaps in patient understanding. This narrative interprofessional review examines the need to educate nurses and pharmacists for early cardiovascular risk recognition through oral health screening and medication review. The review is grounded in the shared-risk-factor approach, recognizing that oral diseases and cardiovascular diseases share several modifiable determinants, including tobacco use, diabetes, unhealthy diet, obesity, low health literacy, and limited access to preventive care. Evidence supports an association between severe periodontitis and cardiovascular disease, although this relationship should be interpreted carefully and not overstated as direct causation. Nurses are strategically positioned to identify oral health indicators, assess symptoms, measure vital signs, provide patient education, reinforce lifestyle modification, and coordinate referrals. Pharmacists complement this role by reviewing cardiovascular and metabolic medications, identifying poor adherence, detecting medication-related risks, educating patients about antihypertensive, antidiabetic, lipid-lowering, antiplatelet, and anticoagulant therapies, and supporting safe medication use in patients who may also require oral or dental care. The review proposes an integrated nurse–pharmacist preventive model in which oral health screening and medication review serve as practical entry points for early cardiovascular risk recognition. In this model, nurses identify oral and clinical warning indicators, pharmacists assess medication-related risks and adherence patterns, and both professionals coordinate referral to dental, primary care, or cardiac services when indicated. ECG-based assessment and cardiac technology may support further evaluation in patients with symptoms or clinically relevant risk profiles, but they should not be used indiscriminately based on oral findings alone. This interprofessional approach may reduce fragmented care, improve patient education, strengthen medication safety, and support more holistic cardiovascular prevention.